2013
DOI: 10.1371/journal.pone.0072604
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells from Human Umbilical Cord Express Preferentially Secreted Factors Related to Neuroprotection, Neurogenesis, and Angiogenesis

Abstract: Mesenchymal stem cells (MSCs) are promising tools for the treatment of diseases such as infarcted myocardia and strokes because of their ability to promote endogenous angiogenesis and neurogenesis via a variety of secreted factors. MSCs found in the Wharton’s jelly of the human umbilical cord are easily obtained and are capable of transplantation without rejection. We isolated MSCs from Wharton’s jelly and bone marrow (WJ-MSCs and BM-MSCs, respectively) and compared their secretomes. It was found that WJ-MSCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
194
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(203 citation statements)
references
References 61 publications
(68 reference statements)
5
194
0
4
Order By: Relevance
“…This effect was mediated only by UCMSCs, excluding the possible role of endothelial progenitor contaminants as previously demonstrated [6]. Indeed, UC-MSCs have a secretome enriched with growth factors and cytokines related to angiogenesis, tissue repair, and wound healing processes when compared with BM-MSCs [52]. Many growth factors linked with angiogenesis were identified in the UC-MSC secretome, such as VEGF-D, PDGF-AA, TGF-b2, b-FGF, and HGF [53].…”
Section: Discussionsupporting
confidence: 53%
“…This effect was mediated only by UCMSCs, excluding the possible role of endothelial progenitor contaminants as previously demonstrated [6]. Indeed, UC-MSCs have a secretome enriched with growth factors and cytokines related to angiogenesis, tissue repair, and wound healing processes when compared with BM-MSCs [52]. Many growth factors linked with angiogenesis were identified in the UC-MSC secretome, such as VEGF-D, PDGF-AA, TGF-b2, b-FGF, and HGF [53].…”
Section: Discussionsupporting
confidence: 53%
“…MM cells were co-cultured with each MSC population and the proliferation was measured at different time points (24,48, and 72 h), as illustrated in Fig. 2A that representatively shows the variations of CFSE in RPMI 8226 cells, whereas Fig.…”
Section: Effect Of Mscs On Myeloma Cell Proliferation and Clonogenicitymentioning
confidence: 99%
“…It has been reported that UCMSCs and BM-MSCs share high similarity in metabolic and functional processes, particularly in their immune processes and biological regulation (19). However, there are differences in the gene expression levels of neurogenesis transcription factors and growth-related genes, amongst others (20) between BM-MSCs and UCMSCs. In this study, we provide evidence of a new role …”
Section: Introductionmentioning
confidence: 99%